2015
DOI: 10.1016/j.colsurfb.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds immobilized on Ti and TiNbHf: AFM-based investigations of biofunctionalization efficiency and cell adhesion

Abstract: Implant materials require optimal biointegration, including strong and stable cell-material interactions from the early stages of implantation. Ti-based alloys with low elastic modulus are attracting a lot of interest for avoiding stress shielding, but their osseointegration potential is still very low. In this study, we report on how cell adhesion is influenced by linear RGD, cyclic RGD, and recombinant fibronectin fragment III8-10 coated on titanium versus a novel low-modulus TiNbHf alloy. The bioactive mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…49 The number and density of molecules immobilized on these surfaces with this method has been reported in a large number of previous studies. 50,51 However 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 adhesion than the whole FN, and similarly to RGDs.…”
Section: One Approach To Improve Osseointegration In Metallic Implantmentioning
confidence: 83%
See 1 more Smart Citation
“…49 The number and density of molecules immobilized on these surfaces with this method has been reported in a large number of previous studies. 50,51 However 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 adhesion than the whole FN, and similarly to RGDs.…”
Section: One Approach To Improve Osseointegration In Metallic Implantmentioning
confidence: 83%
“…48 Moreover, in a recent study we demonstrated that the use of APTES provides a more homogenous layer of biomolecule attachment in both Ti and TiNbHf alloy compared to physisorption. 49 Hence, in the present work APTES was chosen as linker molecule to immobilize the different bioactive molecules onto a recently developed low modulus TiNbHf alloy.…”
Section: One Approach To Improve Osseointegration In Metallic Implantmentioning
confidence: 99%
“…Aminosilanes are used as precursors in this procedure because they are able to bond with hydroxyl groups which may be induced on the oxidized surface of metals [14,15] and, in particular, may be used to functionalize titanium and its alloys [16][17][18][19]. In turn, the resulting amino groups of the functionalized surface are capable of binding themselves to a wide range of biomolecules [20].…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties associated with IS are firstly related with the need for surface activation to induce the appearance of -OH groups at the surface. Activation requires a pre-processing of the material by either immersion in acid [19,24] or with an oxygen plasma treatment [16]. Secondly, IS tends to result in a relatively low concentration of amine functional groups on the surface which, in addition, may be non-homogeneously distributed.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive approach is to take advantage of natural molecules in the human body, e.g., elastin (42,43). The elastin-like recombinamers can be decorated with growth factors or other molecules to promote islet cell survival and revascularization of the surface of the encapsulated islet after implantation (44,45). The covalent binding induced between the various layers would provide stability and longevity.…”
Section: Influence Of the Dead Space Within The Encapsulation Devicementioning
confidence: 99%